Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Profil génétique et prévalence de la fibrose kystique dans les communautés acadiennes et francophones des Maritimes - Chappe, Frédéric; McGrath, Karla; Robinson, Walter; Chappe, Valérie (Francophone d'Amérique, 2009)
Nous évaluons ici la situation des Acadiens et des francophones des provinces maritimes (Nouvelle-Écosse, Nouveau-Brunswick, Île-du-Prince-Édouard) face à la fibrose kystique, la maladie génétique létale la plus répandue en Amérique du Nord. Nos résultats indiquent que plusieurs familles acadiennes et francophones sont touchées par cette maladie et qu’il existe un besoin de documentation et de services en français, spécifiques aux communautés acadiennes. Des disparités régionales ont été observées pour l’âge au diagnostic et le profil génétique, notamment dans les régions à majorité francophone. Cette analyse confirme le besoin d’études spécifiques sur la santé des Acadiens et des francophones des Maritimes.

Préparer le terrain pour la santé en français. Rapport final - Duguay, Lise; Fortin, Pierrette; Hendriks, Edouard; Losier, Barbara; Pinet, Léo-Paul; Schofield, Aurel; St-Pierre-Ellis, Lyne; Thébeau, Marcel; Thériault, Bernadette; Vienneau, Gilles (La Société Santé et Mieux-être en français du Nouveau-Brunswick, 2007)

Is Francophone language status associated with diffences in the health services use of rural Nova Scotians? - Langille, Donald; Rainham, Daniel; Kisely, Steve (Canadian Journal of Public Health, 2012)
L’étude a pour objet de vérifier empiriquement la validité d’un modèle théorique qui propose un système de relations liant la construction de l’identité ethnolinguistique à la satisfaction de vie, un aspect du mieux-être psychologique, et à l’autoévaluation de sa santé. Un échantillon de 8 124 élèves du secondaire, provenant de 30 conseils scolaires francophones situés à l’extérieur du Québec, a participé à l’étude. Les résultats sont conformes au modèle fondé sur la théorie de l’autodétermination, qui stipule que lorsque la construction identitaire se fait dans un contexte d’appui à des besoins psychologiques de base, elle est reliée au mieux-être psychologique de la personne. Abstract

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Impact de la crise de la COVID-19 sur les familles francophones dans les Prairies canadiennes - Leis, Anne; De Moissac, Danielle; Proulx-Cullen, Elyse; Gnidehou, Sedami; Marchak, Kristan A.; Keough, Catelyn; Chaput, Mélanie; Turgeon, Marianne (Minorités linguistiques et société, 2025)
Contexte et but. Dans le contexte linguistique minoritaire où l’accès à des services en français est un défi, l’étude voulait documenter dans quelle mesure la crise de la pandémie avait eu un impact sur les familles francophones au Manitoba, Saskatchewan et Alberta. Méthodes. À partir des informations recueillies lors de 6 World Café du Monde, un sondage a été créé et distribué en ligne aux membres d’organismes francophones dans ces provinces. Des analyses descriptives et de régression ont été menées. Résultats. Des 319 familles, la grande majorité a reconnu l’impact négatif et anxiogène de la pandémie. Plusieurs facteurs de risque ont été identifiés : une compréhension moyenne ou faible de l’anglais, la déconnexion avec la communauté francophone locale, la difficulté de vivre en français en famille et de suivre la scolarité de ses enfants à la maison. Conclusion. La pandémie a été un défi pour les familles francophones des Prairies. Des ressources accrues en français et des politiques de soutien sont recommandées. , Background and aim. Within the linguistic minority context where access to services in French is a challenge, the study aimed to document to what extent the pandemic had an impact on Francophone families in Manitoba, Saskatchewan and Alberta. Methods. Based on the qualitative analysis of data collected in 6 World Cafés, an on-line survey was distributed to members of Francophone organizations in these provinces. Descriptive and regression analyses were conducted. Results. Of 319 families, the majority recognized the negative and anxiety provoking aspects of the pandemic. Several risk factors were identified: an average or below average mastery of English, isolation from the local Francophone community, difficulty with living in French with their family and supporting children’s education at home. Conclusion. The pandemic was a challenge for Francophone families in the Prairies. Additional resources in French and supportive policies are recommended.

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services